1983
DOI: 10.1210/jcem-57-5-1074
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Polypeptide Responses to Protein Meal Challenges in Obese but Otherwise Normal Children and Obese Children with Prader-Willi Syndrome*

Abstract: Children with hyperphagia and obesity of Prader-Willi syndrome (PWS) have previously been shown to have blunted pancreatic polypeptide (PP) response to low protein meal stimulation. To evaluate the effects of various protein challenges on PP release in children with PWS, we administered both a low protein (0.2 g/kg) and a high protein (2.0 g/kg) meal stimulation test to 12 children previously diagnosed as having PWS and to an age- and weight-matched group of 19 obese but otherwise normal children. Serum sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 17 publications
2
38
2
Order By: Relevance
“…However such interventions may also lower circulating anorexigenic gastroenteropancreatic hormones which may complicate their interpretation (De et al, 2008;Tan et al, 2004). Thus although other pathological defects are felt to cause or contribute to hyperphagia in PWS, including reduced circulating anorexigenic pancreatic polypeptide levels (Zipf et al, 1983), hypothalamic dysfunction (Goldstone et al, 2003;Goldstone, 2004), defects in brain reward and satiety systems (Hinton et al, 2006;Holsen et al, 2006;Miller et al, 2007), and decreased brain-derived neurotrophic factor (BDNF) which functions downstream of leptin and POMC/MC4R signalling (Han et al, 2010), it will need the clinical development of ghrelin antagonists or GOAT inhibitors to be able to definitively assess the role of hyperghrelinemia in the hyperphagia of PWS.…”
mentioning
confidence: 99%
“…However such interventions may also lower circulating anorexigenic gastroenteropancreatic hormones which may complicate their interpretation (De et al, 2008;Tan et al, 2004). Thus although other pathological defects are felt to cause or contribute to hyperphagia in PWS, including reduced circulating anorexigenic pancreatic polypeptide levels (Zipf et al, 1983), hypothalamic dysfunction (Goldstone et al, 2003;Goldstone, 2004), defects in brain reward and satiety systems (Hinton et al, 2006;Holsen et al, 2006;Miller et al, 2007), and decreased brain-derived neurotrophic factor (BDNF) which functions downstream of leptin and POMC/MC4R signalling (Han et al, 2010), it will need the clinical development of ghrelin antagonists or GOAT inhibitors to be able to definitively assess the role of hyperghrelinemia in the hyperphagia of PWS.…”
mentioning
confidence: 99%
“…Pancreatic polypeptide Previous studies have found that, compared with non-obese and obese controls, fasting levels of PP are either normal 22,23,45 or decreased, 10,21,35 and post-prandial levels decreased, 10,21 --23,35,45 in both children over the age of 5 --7 years and adults with PWS. Although eating behaviour was rarely described in the non-adult studies, most of the children did have marked obesity.…”
Section: Discussionmentioning
confidence: 99%
“…PP does appear to be an efficacious treatment for hyperphagia secondary to PraderWilli syndrome. These patients have blunted basal and post-prandial PP responses which may contribute to their hyperphagia and obesity (Zipf et al 1981(Zipf et al , 1983. A twice-daily 'replacement' of PP by infusion results in a 12% reduction in food intake during the therapy (Berntson et al 1993).…”
Section: Pp-fold Peptidesmentioning
confidence: 99%